the effect of a program for the development of neuromuscular compatibility on the development of social interaction in deaf and dumb children 12-15 years - LAKHDAR, ABBAS; KIHAL, ismail; BOUNECHADDA, YACINE (Journal of Social Sciences and Humanities, 2022)
Our study aimed to reveal the effect of an adapted program to develop neuromuscular compatibility on the development of social interaction among deaf and dumb children so that we conducted an exploratory study at the School for Blind Children in Djelfa, and we selected the sample so that our sample consisted of 20 deaf and dumb children between the ages of 12 to 15 years, Then the neuromuscular compatibility exercises appropriate for this age group were chosen. The exercises included numbered circuit testing, throwing and receiving balls on the wall and running ball test between cones. We used the descriptive approach in the statistical method, and we used the social interaction scale. There is a direct impact of the adapted program to develop neuromuscular compatibility in developing communication skills, advocacy and support skills, as well as sympathy and participation skills for deaf and dumb children (9-12) years.